1)na3po4 + 3agno3 = ag3po4↓ + 3nano3
3na(+) + po4 + 3ag(+) + 3no3(-) = ag3po4↓ + 3 na(+) + 3no3(-)
3ag(+) + po4 = ag3po4↓
2)не идет реакция
3)сaco3 + 2hno3 = ca(no3)2 + h2o + co2↑
сaco3 + 2h(+) + 2no3(-) = ca(2+) + 2no3(-) + h2o + co2↑
сaco3 + 2h(+) = ca(2+) + h2o + co2↑
4)cu(no3)2 + zn = zn(no3)2 + cu
cu(2+) + 2no3(-) + zn(0) = zn(+) + 2no3(-) + cu(0)
cu(2+) + zn(0) = zn(+) + cu(0)
5)не идет реакция
6)fe(no3)2 + 2koh = fe(oh)2↓ + 2kno3
fe(2+) + 2no3(-) + 2k(+) + 2oh(-) = fe(oh)2↓ + 2k(+) + 2no3(-)
fe(2+) + 2oh(-) = fe(oh)2↓
7) k2sio3 + 2hcl = h2sio3↓ + 2kcl
2k(+) + sio3(2-) + 2h(+) + 2cl(-) = h2sio3↓ + 2k(+) + 2cl(-)
2h(+) + sio3(2-) = h2sio3↓
{[AgI]m · nI– · (n-x)K+}x– · x K+ (изб KI)
Zn + CuCl2 > ZnCl2 + Cu
Cu + HCl ≠
Cu + Mg(NO3)2 ≠
2AI + 3H2SO4(разб.) ---> AI2(SO4)3 + 3H2↑
Hg + 2H2SO4(конц.) ---> HgSO4 + SO2↑ + 2H2O
Cu + 2AgNO3 ---> Cu(NO3)2 + 2Ag
Ag + H2O ≠
Ca + 2H2O ---> Ca(OH)2 + H2↑